2022
DOI: 10.1155/2022/9252319
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Therapeutic Mechanism of Adipose-Derived Mesenchymal Stem Cells in Osteoarthritis via Upregulation of BTG2

Abstract: Background. Osteoarthritis (OA) is a debilitating and degenerative joint disease, which is characterized by progressive destruction of articular cartilage. Mesenchymal stem cells (MSCs) have been implicated in the treatment of OA. However, the function of adipose-derived MSCs (AD-MSCs) in OA and its underlying mechanism remain obscure. Aim. We aimed to explore the function of AD-MSCs in OA and investigate its potential regulatory mechanism. Methods. A guinea pig model of OA was constructed. AD-MSCs injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition, Tob2 could also inhibit the formation of osteoclasts by interacting with the vitamin D receptor (VDR) to suppress the expression of the receptor activator of the nuclear factor-kappa B ligand (RANKL) [109]. BTG2 has been shown to be significantly downregulated in the cartilage of osteoarthritis animal models [110].…”
Section: Circrnas and Bone Related Diseasesmentioning
confidence: 99%
“…In addition, Tob2 could also inhibit the formation of osteoclasts by interacting with the vitamin D receptor (VDR) to suppress the expression of the receptor activator of the nuclear factor-kappa B ligand (RANKL) [109]. BTG2 has been shown to be significantly downregulated in the cartilage of osteoarthritis animal models [110].…”
Section: Circrnas and Bone Related Diseasesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%